Bankruptcy risk in financial depository intermediaries : assessing regulatory effects - Koehn, Michael F. (Lexington, Mass. : Lexington Books, 1979)
The purpose of this study is to investigate the effects that solvency regulations have on an intermediary's investment opportunity set, its quality of earnings, and its probability of bankruptcy
"An Arthur D. Little book."
Includes index.
Bibliography: p. 149-152.
osc 11/05/2018
Loans
Keywords: Banks and banking; Banking law; Financial institutions; Bank failures